Fulminating Colitis Multiple Drilling: Case Report - Mendoza-Pineda, Nancy; García-Sánchez, Morelos Adolfo; De La Fuente González, Mireya; Estrada-Rodríguez, María Isabel; Terán-Estrella, Mara Luz; Urbina-Cabello, José Jesús; Jiménez-Bonola, Yamileth; Herrera-Medina, Jessica Montserrat; Castillo-García, Giselle; Flores-Pazos, Mauricio Israel; Méndez-Barrón, Gema; Zapien-Rangel, Mario Alberto; et al. (British Journal of Healthcare and Medical Research, 2023)
Introduction: fulminant colitis is a serious infection characterized by the presence of hypotension, shock and/or toxic megacolon. The nobility of the organ is exhausted once its chronic homeostatic adaptation breaks out. Objective: presentation of a case and review of the literature. 44-year-old male in the emergency department, without any significant history. Inmate of the prison system. Reports marijuana use. Bisexual. Conscious, cachectic, with dry mucous membranes, pale integuments, abdominal facies, cardiopulmonary without apparent compromise. Abdomen with colicky pain, increased peristalsis, tympanism present, no visceromegaly is palpable, but with clear signs of an acute abdomen, so he was immediately admitted to the operating room, finding fecal peritonitis due to multiple perforations of the entire colon from the cecum. up to the upper third of the rectum, colectomy and protectomy of the upper third are performed. Histopathology reports “perforated colon in multiple sites with six perforations due to chronic ulcerated amoebic colitis.” Discussion: Fulminant amoebic colitis is a rare complication of amebiasis associated with high mortality and it can occur in more than 50% of cases with severe colitis. Its pathogenicity is associated with its extremely polymorphic genetic structure of this parasite, determined by high-resolution genotyping methods. Conclusion: the defense mechanisms of the target organ and the eccentric pathogenicity of the parasite, together create a symbiotic chronicity, which extremely postpones the decline of the patient's homeostasis, until a catastrophic and/or fatal scenario. The treatment of fulminant amoebic colitis is surgical.